Day 3 Thu, February 11, 2016 2016
DOI: 10.2118/179110-ms
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ash Beds on Production in Eagle Ford Shale

Abstract: The Eagle Ford shale contains both kaolinite-and smectite-rich altered ash beds that present challenges for completion and production. Considering the five Eagle Ford units (A-E), the ash beds occur in the B unit. The B unit is divided into five subunits; B1 and B2 are characterized by the highest total organic carbon (TOC) whereas B3-B5 have a higher frequency of ash beds. The impact of these ash beds is not yet fully understood, but acquired horizontal production log measurements indicate that the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The other application known to the authors is in unconventional shale gas samples, sometimes volcanic ash beds are found (can be mm or meters thick) and these are known to fluoresce easily under UV excitation. A well-known example are the ash beds found in the Cretaceous Eagle Ford Shale of Texas, USA; studies indicate it has 55-110 volcanic ash beds and has been the topic/mentioned in multiple studies because of its impact on petroleum production (Amin et al, 2021;Lehrmann et al, 2019;Zeng et al, 2018;Xu et al, 2016;Lock, 2014) because it affects the fracture propagation that result from fracking and is easily detected/verified by fluorescence in drill core or outcrop.…”
Section: Discussionmentioning
confidence: 99%
“…The other application known to the authors is in unconventional shale gas samples, sometimes volcanic ash beds are found (can be mm or meters thick) and these are known to fluoresce easily under UV excitation. A well-known example are the ash beds found in the Cretaceous Eagle Ford Shale of Texas, USA; studies indicate it has 55-110 volcanic ash beds and has been the topic/mentioned in multiple studies because of its impact on petroleum production (Amin et al, 2021;Lehrmann et al, 2019;Zeng et al, 2018;Xu et al, 2016;Lock, 2014) because it affects the fracture propagation that result from fracking and is easily detected/verified by fluorescence in drill core or outcrop.…”
Section: Discussionmentioning
confidence: 99%